KOMITE AUDIT, INTENSITAS MODAL, UKURAN PERUSAHAAN DAN TAX AVOIDANCE: STUDI EMPIRIS DI INDONESIA - Rahmawati Hanny Yustrianthe (AKUNTANSI DEWANTARA, 2022)
Tax avoidance is an effort to minimize the nominal tax burden by finding loopholes in taxation provisions in a country. This study aims to determine the effect of the audit committee, capital intensity and company size on tax avoidance. This research is a causal comparative research method. The independent variable of this study is the audit committee, capital intensity, and company size, while the dependent variable is tax avoidance. The audit committee variable is measured by counting the number of audit committees in a company. The capital intensity variable is measured using the fixed asset intensity ratio. The firm size variable is measured using Ln (Total Assets). Tax avoidance is measured using the Effective Tax Rate (ETR). The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2019. The sample in this study using purposive sampling method and obtained 44 companies. The data analysis used was descriptive analysis followed by multiple linear regression analysis. The results show that the audit committee has a negative and significant effect on tax avoidance, capital intensity has a positive and significant effect on tax avoidance, company size has a negative and significant effect on tax avoidance. Keywords: AuditÂ  committee; capital intensity; company size; and tax avoidance Â